Saturated Red Electroluminescence From Thermally Activated Delayed Fluorescence Conjugated Polymers - Zhan, Hongmei; Wang, Yanjie; Li, Kuofei; Chen, Yuannan; Yi, Xiaohu; Bai, Keyan; Xie, Guohua; Cheng, Yanxiang (Frontiers in Chemistry, 2020)
Two sets of conjugated polymers PFSOTAQx and PCzSOTAQx with anthraquinone groups as pendant acceptors were designed and synthesized. The acceptor is tethered to an diphenylamine group via a phenylene bridge, constructing a TADF unit (TAQ), which is embedded into the polymer backbone through its donor fragment, while the backbone is composed of dibenzothiophene-S,S-dioxide (SO) and 2,7-fluorene (F) or 2,7-carbazole (Cz) groups. The polymers show distinct TADF characteristics, confirmed by transient photoluminescence spectra and theoretical calculations. The carbazole-based polymers PCzSOTAQx exhibit shorter delay lifetimes and lower energy emission relative to the fluorene-based polymers PFSOTAQx. The non-doped organic light-emitting diodes fabricated via solution processing approach produce efficient red emissions with the wavelengths of 625-646 nm. PCzSOTAQ2 with 2% molar content of the TAQ unit exhibits the best maximum external quantum efficiency of 13.6% and saturated red electroluminescence with the Commission Internationale de l’Eclairage coordinates of (0.62, 0.37).